Chameleons of Kurdish Turkey: Ethnographic reflections on a queer counter/insurgency - Karakuş, Emrah (Anthropology today, 2022)
This article examines the intimacies and socialities of queer and transgender Kurds shaped by the sex work economy and ongoing conflict between the Turkish state and the Kurdistan Workers' Party (PKK). In their struggle for livelihoods, they manoeuvre through various forms of surveillance by the state and one another, necessitating what some call a chameleon subjectivity that protects one from surveillance. Central to the dynamics of their socialities are norms based on how they paid the price (bedel) to earn the right to be in the sex work economy. These everyday socialities are now intimately and increasingly interwoven with the institutions, discourses and practices of securitization in Kurdish Turkey, turning queer Kurds into particular kinds of political subjects.